Books aren't for bears - Barry, Mark (Children's author); Halford, Katy (2023)
Bear learns to read from a book he finds in the woods, so, hoping for more, he sets out for the city, but people tell him that books are not for bears and chase him away--except for the librarian, who understands.
Ages 4 to 8.
Grades K-1.
Keywords: Bears -- Juvenile fiction; Books and reading -- Juvenile fiction; Librarians -- Juvenile fiction; Libraries -- Juvenile fiction; Bears -- Fiction; Books and reading -- Fiction; Librarians -- Fiction; Libraries -- Fiction